The Need for Entrepreneurial Education in Jordan- An Empirical Investigation - Sandri, Serena (Jordan Journal of Business Administration, 2016)
Entrepreneurial or entrepreneurship education aims at developing an interdisciplinary mindset and a whole set of opportunity recognition and problem solving skills that go beyond the promotion of startups and business ventures management. Through the Rethinking Education Communication and the Entrepreneurship 2020 Action Plan, the European Commission has explicitly recognized the importance of investing into entrepreneurship education, as a response to the challenges posed to the educational system by globalization, increased international concurrence, and youth unemployment. Jordan also faces these challenges, but substantial and coordinated efforts in entrepreneurial education are still missing.We believe that entrepreneurial education may represent a way of improving the dramatic situation with youth unemployment, boosting the structurally underdeveloped private sector, and preparing a new generation of youngsters capable of constructively adding to the labor market, by recognizing and exploiting new opportunities in an entre- and intrapreneurial way. The present analysis reviews and elaborates the concept of entrepreneurial education and empirically evaluates the need and potential of entrepreneurial education in Jordan. This is done via a questionnaire study run over a sample of undergraduate students from public universities in Jordan. Results are benchmarked to the findings of a large scale study run over European students in the frame of the ASTEE project (Moberg et al., 2014).